A continuous sampling plan based on EWMA Control Chart Rules. Issue 1 (2nd January 2016) - Eleftheriou, Mavroudis; Farmakis, Nikolaos
Abstract: In this paper, we introduce and study a new continuous sampling plan (CSP), based on alternative switching rules. The innovation of the proposed CSP, called CSP-EWMA, lies on the use of an one-sided geometric EWMA control chart for triggering the alternation between the phase of 100% inspection and sampling. The function of the EWMA control chart and its adaptation to the algorithmic procedure of CSPs is thoroughly examined and theoretically established. Typical performance measures of the proposed sampling plan are extracted using analytical methods stemming from modelling it as a Markov chain. The evaluation of the proposed CSP-EWMA is attempted through comparisons with the prevailing CSP-1 and CSP-CUSUM. Additionally, an algorithm of optimally designing the CSP-EWMA is provided and supported by case studies for various parameter values.